Seawater utilization through hybrid photocatalysis-electrocoagulation process using pumice-supported g-C3N4/BiOBr for hydrogen production and methylene blue decolorization - Julius Rainer Sudianto; Reno Pratiwi; Bambang Heru Susanto; Slamet Slamet (Center of Biomass & Renewable Energy (CBIORE), 2026)
This study investigated the simultaneous photocatalysis-electrocoagulation process using pumice-supported g-C3N4/BiOBr nanocomposites in seawater treatment to remove organic pollutants and generate hydrogen gas. The photocatalyst nanocomposite was synthesized via coprecipitation and immobilized on the pumice surface to enhance light exposure and facilitate catalyst recovery. The performance of the hybrid system was evaluated under various operational parameters, including applied voltage, seawater concentration, and pH. The results showed that the combined process outperformed the individual photocatalysis and electrocoagulation systems. Optimal performance was achieved at pH 3 and 15% seawater concentration, resulting in 99.37% methylene blue decolorization and 211 mL of hydrogen within 2 hours. At higher salinities and lower pH, increased coagulant formation caused a shadowing effect, limiting photocatalytic efficiency despite continued hydrogen evolution. The XPS (X-Ray Photoelectron Spectroscopy) characterization of the photocatalyst material, demonstrated the successful formation of a nanocomposite with a stable surface chemistry. Photoluminescence analysis confirmed that the charge separation mechanism could be enhanced, suppressing the recombination rate and being the primary reason for the enhanced photocatalysis process, although interfacial electronic interactions remained limited. Overall, this study demonstrates that the pumice-supported g-C₃N₄/BiOBr photocatalyst integrated with electrocoagulation provides an effective and stable platform for seawater-based hydrogen production and organic pollutant removal.